Patient perspectives towards skin of color clinics: results from a survey study - Severine Cao, MD; Reinie Thomas, BA; Meghan Mansour, BS; Juliana L. Ramirez, BA; Grace Hile, MD; Mari Paz Castanedo-Tardan, MD; Milad Eshaq, MD (Wolters Kluwer, 2024)
Background:. Skin of color clinics (SOCCs) are dermatology clinics that provide specialized care for patients with melanated skin. Little is known about patient perceptions and attitudes toward these clinics. Objective:. We sought to perform a survey study to assess the opinions of patients of color previously seen in our dermatology department toward SOCC. Methods:. A 14-question survey was sent by email to patients of color seen at our institution between January 1, 2015 and December 31, 2021. Results:. Out of 264 participants who completed the survey, 176 (66.7%) indicated they would prefer to be seen in a SOCC and 88 (33.3%) preferred to be seen in a general dermatology clinic (GDC). Clinic choice varied significantly by ethnicity, with Black/African American participants being the most likely to prefer SOCC over GDC than other races/ethnicities. Those interested in SOCC were primarily motivated by a search for expertise in the skin of color (SOC) and did not have a preference for the skin color of the SOCC dermatologist. Those interested in GDC were happy with their current care. Limitations:. This study was limited by the single-center design and sample bias. Conclusion:. Our results overall provide positive patient feedback for the creation of SOCCs as centers for expertise in SOC. The preference for SOCC varied by race/ethnicity, highlighting that clinic choice is best left to the patient.